Job Burnout: A Mediation between Emotional Intelligence and Turnover Intention - Kartono Kartono; Hilmiana Hilmiana (Jurnal Bisnis Manajemen, 2018)
The emotional intelligence of employees can make employees have the desire to the turnover intention which can also be influenced by the level of job burnout employees. This research aims to investigate the effect of emotional intelligence on the turnover intention with job burnout as the mediating variable. This study uses a quantitative analysis method which aims to analyze the relationship between the observed variables and to confirm the theory using PLS-SEM analysis (Partial Least Square - Structural Equation Modeling). Respondent consists of 233 employees of PD. Bank BPR West Java who were selected using random sampling technique. The results showed that emotional intelligence, consisting of social competence and personal competence, positively affect turnover intention, characterized by the behaviors of thinking to quit, job search, and intending to quit. Emotional intelligence, consisting of social competence and personal competence, positively influences job burnout which can be seen from the aspect of exhaustion, depersonalization, and declining achievement. Employees experiencing a high level of emotional exhaustion will be likely to quit and look for new career opportunities. In other words, the higher the level of job burnout is, the higher the tendency of the employee to quit becomes.